2022
DOI: 10.3390/antibiotics11121747
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tonsil Tissues from Patients Diagnosed with Chronic Tonsillitis—Microbiological Profile, Biofilm-Forming Capacity and Histology

Abstract: Chronic tonsillitis (CT) is a global health issue which can impair patient’s quality of life and has an important socioeconomic impact due to the nonrational use of antibiotics, increased antimicrobial resistance and frequent need for surgical treatment. In order to isolate and identify the causing agents of CT, a total of 79 postoperative palatine and adenoid tissue samples were obtained from the ENT Clinic, KBC Zvezdara, Belgrade, Serbia. Culture identification was performed by MALDI-TOF MS and the Staphyloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…The following oral isolates of Gram-positive ( Micrococcus luteus, Rothia mucilagenosa, Streptococcus agalactiae, Streptococcus angiosus, Streptococcus conselatus, Streptococcus dysgalactiae, Streptococcus oralis, Streptococcus parasanquinis, Streptococcus pseudopneumoniae, Streptococcus pyogenes, Streptococcus salivarius, Staphylococcus aureus, Staphylococcus hominis, Staphylococcus warneri ) and Gram-negative ( Stenotrophomonas maltophilia and Enterobacter cloacae ) bacteria were used. They were obtained from the tonsillar tissue of patients, at the Otorhinolaryngology clinic at Clinical Hospital Center Zvezdara, Belgrade, Serbia [ 26 ]. Tested bacteria were deposited at the Mycological Laboratory, Department of Plant Physiology, Institute for Biological Research “Siniša Stanković”, National Institute of the Republic of Serbia, University of Belgrade.…”
Section: Methodsmentioning
confidence: 99%
“…The following oral isolates of Gram-positive ( Micrococcus luteus, Rothia mucilagenosa, Streptococcus agalactiae, Streptococcus angiosus, Streptococcus conselatus, Streptococcus dysgalactiae, Streptococcus oralis, Streptococcus parasanquinis, Streptococcus pseudopneumoniae, Streptococcus pyogenes, Streptococcus salivarius, Staphylococcus aureus, Staphylococcus hominis, Staphylococcus warneri ) and Gram-negative ( Stenotrophomonas maltophilia and Enterobacter cloacae ) bacteria were used. They were obtained from the tonsillar tissue of patients, at the Otorhinolaryngology clinic at Clinical Hospital Center Zvezdara, Belgrade, Serbia [ 26 ]. Tested bacteria were deposited at the Mycological Laboratory, Department of Plant Physiology, Institute for Biological Research “Siniša Stanković”, National Institute of the Republic of Serbia, University of Belgrade.…”
Section: Methodsmentioning
confidence: 99%
“…Biofilms play a significant role in LPR and laryngitis, contributing to chronic infections and inflammation in the larynx and pharynx. In LPR, biofilms can form on the laryngeal tissues due to exposure to refluxed microorganisms and irritants, resulting in prolonged diffuse laryngeal inflammation often diagnosed as chronic laryngitis [ 23 ]. The biofilms in the larynx can exacerbate the inflammatory response and contribute to the persistence of laryngitis symptoms, impacting vocal quality and overall laryngeal health.…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, Swidsinski et al [ 46 ] examined the tonsil and adenoid tissues and found that many patients had multiple areas of ongoing purulent infection within these tissues. The traditional notion that chronic adenotonsillitis is solely caused by a single bacterial species colonizing the tissue surface is being challenged [ 47 ]. Instead, tissue hyperplasia and enlargement may be influenced by a variety of opportunistic, commensal, and pathogenic microorganisms, as well as the immune system’s response to them.…”
Section: Microbiology Of Adenoids and Tonsilsmentioning
confidence: 99%